ANALISIS STRATEGI PENERJEMAHAN TEKS BAHASA INGGRIS-BAHASA INDONESIA: STUDI KASUS MATA KULIAH BAHASA INGGRIS UNTUK PENGAJARAN MATEMATIKA - Khamida Siti Nur Atiqoh (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2020)
This study aims to analyze students' strategies in translating English-Indonesian mathematics texts. The study was conducted on students of the Mathematics Education study program in the English for Teaching Mathematics course. The research method is a qualitative descriptive method with data analysis units of text translation as many as 31 students. The translation strategy uses 2 stages, namely the comprehension strategies, referring to the analysis of the source text, and the production strategies, referring to the production of the translated text. The results of the study reveal that in general students have been able to carry out comprehension strategies well as evidenced by their good understanding of mathematics and mathematics learning vocabulary, while the production strategy stage is still lacking, i.e the results of the production of a full sentence translation text in paragraph form involving mathematical vocabulary still too 'stiff'. The conclusion of this study is that the factors of experience and student habituation in reading mathematics texts in English have an effect on the ability in understanding strategies and production strategies.